FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PETUGAS PENYAPU JALAN DINAS LINGKUNGAN HIDUP KOTA JAMBI TAHUN 2020 - Ulanda Nita Kurnia; Asparian Asparian; Lia Nurdini (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2021)
ABSTRACT Improving the health and safety of works is hazards control by using personal protective equipment (PPE) with thw work occupational standard health and safety program. There are several personal factors associated with workers using personal protective equipment (PPE) at work, including knowledge, attitudes, age, education level and years of service. The reseach objective was determinan serval factor reated to using personal protective equipment (PPE) of road sweepers in Jambi City. This type of research was a quantitative study by using a Cross Sectional approach. The results of this reseach a relations between most of responden have of female gender 92,0%, with material status of a married worker 96,0% and the work area street sweeping officers in Telanai 26,7%, work area in Kota Baru 17,3% and Thehok 13,3%. Fakctor related to of personal protective equipment (PPE) are knowledge (PR=1,600, 95% CI=1,223 – 2,093), attitude (PR=1,444, 95% CI=1,172-1,781), years of service (PR=1,071 95% CI=0,758-1,513 ) Factors no related to use of personal protective equipment (PPE) age (PR=1,194, CI=0,740–1,927), education level (PR=1,219, 95% CI 0,928-1,603). There were a relations between knowledge, attitude and years of service of personal protective equipment (PPE). There is no relationship between age and education level with the use personal protective equipment. Keywords: Knowledge, Attitude, PPE, Officer Street Sweeper   ABSTRAK Salah satu upaya meningkatkan kesehatan dan keselamatan tenaga kerja yaitu dengan pengendalian bahaya-bahaya yang mungkin terjadi saat berada di lingkungan kerja dengan menggunakan alat pelindung diri sesuai dengan standar yang telah ditentukan dalam program keselamatan dan kesehatan kerja (K3). Banyak faktor yang mempengaruhi penggunaan alat pelindung diri (APD) meliputi penge- tahuan, sikap, umur, tingkat pendidikan dan masa kerja. Tujuan penelitian ini adalah untuk mengetahui beberapa faktor yang berhubungan dengan penggunaan alat pelindung diri (APD) pada petugas penyapu jalan Dinas Lingkunga Hidup Kota Jambi. Penelitian ini menggunakan desaincase control. Populasi adalah seluruh petugas penyapu jalan Kota Jambi. Faktor yang berhubungan dengan penggunaan APD pada petugas peyapu jalan yaitu pengetahuan pengetahuan (PR = 1,600, 95% CI = 1,223 – 2,093), sikap (PR = 1,444, 95% CI = 1,172-1,781) dan masa kerja (PR = 1,071 95% CI = 0,758-1,513) dan masa kerja (PR = 1,071 95% CI = 0,758-1,513) dan faktor yang tidak berhubungan yaitu umur (PR = 1,194 CI = 0,740 – 1,927), tingkat pendidikan (PR = 1,219 95% CI 0,928-1,603). Maka dapat disimpulkan ada hubungan antarapengetahuan, sikap dan   masa kerja terhadap   penggunaan alat pelindung diri (APD). Kata Kunci: Pengetahuan, sikap, APD, penyapu jalan